Language change and linguistic theory. - Miller, D. Gary (Oxford University Press, 2011)
This book investigates a large range of changes and their motivations in all parts of the grammar and lexicon. The core argument is that, in the absence of a Grand Unification Theory in linguistics, a natural language changes. Changes occur in successive formal grammars.